Optimization of Flaxseed Meal Protein Extraction Process and Study of Protein Structure and Functional Properties - Tingting LUO; Jingjing LI; Haiyue HU; Yajun HE; Yuzhuo LI; Lingxuan ZHAO; Lina WANG; Chen YANG; Jianming WANG (Shipin gongye ke-ji)
To enhance the utilization value of flaxseed meal protein (FPI), alkali solubilization and acid precipitation method was used to extract FPI from flaxseed meal (FM). The extraction process of FPI was optimized through single-factor and response surface methodology experiments. The structure of FPI was characterized, and the functional properties of FPI was analyzed. The results showed that the optimal extraction conditions of FPI were as follows: Extraction pH10, extraction temperature 45 ℃, extraction time 90 min, and material-liquid ratio 1:25 g/mL. At these conditions, the protein extraction rate was 22.69%. Compared with FM, the relative content of β-sheet and α-helix in FPI decreased by 10.57% and 0.61% respectively, and its microstructure exhibited typical freeze-dried plate-like structure and irregular scale-like structure. In addition, the functional properties of FPI were highly dependent on pH, when the pH away from the isoelectric point of FPI (pH4), there was a significant improvement in its functional properties. At pH8, FPI exhibited optimal solubility (99.52%), water-holding capacity (8.87 g/g), emulsifying activity (8.92 m2/g), and emulsion stability (122.58 min). At pH7, the foaming capacity (48.65%) and foaming stability (94.94%) of FPI were optimal, while the FPI gel showed maximal hardness (137.03 g), elasticity (0.829), and water holding capacity (99.29%), indicating its optimal gel properties. This study provides a theoretical basis for the development and utilization of FPI as emulsifier or gel in food or medicine, and is conducive to improving the utilization value of FPI.